Plant diversity patterns along an elevation gradient: the relative impact of environmental and spatial variation on plant diversity and assembly in arid and semi-arid regions - He, Xinrui; Arif, Muhammad; Zheng, Jie; Ni, Xilu; Yuan, Zhongxun; Zhu, Qiang; Wang, Jifei; Ding, Dongdong; Li, Changxiao (Frontiers in Environmental Science, 2023)
The spatial distribution pattern of species diversity and its driving variables are essential to understanding how biodiversity will respond to the threat of future climatic instability. This study examines how the alpha and beta diversity indices vary along the elevation gradient and which factors are more responsible for arid and semi-arid plant diversity and community assembly. There were 121 species from 90 genera and 42 families found at elevations ranging from 1,200 to 2,600 m within the Ningxia Helan Mountain National Nature Reserve in China. These were primarily shrubs and herbs with characteristics adapted to extreme temperatures. The diversity of both the shrub layer and the herb layer was highest at mid-elevation, underscoring the importance of protecting mid-elevation ecosystems. Climatic distance and topographic distance were more influential than spatial distance in driving the species composition change of shrubs and herbs. In the herb layer, climatic, topographic, and spatial factors contributed more to community assembly than shrub communities. In this case, improving the environment in the community or introducing herbs could help the restoration of these places. These findings provide insight into biogeographic patterns, biodiversity growth mechanisms, and community formation processes. Moreover, it can improve projections of climate change within and across ecosystems and provide the scientific basis for the use and management of plant resources in arid and semi-arid regions.